Stretching out the Australasian microtektite strewn field in Victoria Land Transantarctic Mountains - Folco, Luigi; D'Orazio, Massimo; Gemelli, Maurizio; ROCHETTE, Pierre (Polar Science, 2016)
International audience Petrographic and geochemical studies of microtektites collected in newly explored summit plateaus of the Transantarctic Mountains (i.e., Schroeder Spur, Killer Nunatak, Miller Butte in the inland catchment of the Rennick Glacier, and Allan Hills, in the inland catchment of the Mackay-David Glaciers) document a regional distribution of Australasian microtektites in Victoria Land. A geochemical comparison with Australasian microtektites from deep sea sediments at lower latitudes identifies a possible projectile geochemical signature for the first time, and confirms that Transantarctic Mountains microtektites experienced higher thermal regimes. Ballistic calculations reveal that the extraordinary distance of the Transantarctic Mountains microtektites from the hypothetical impact location in Indochina (similar to 11,000 km) could be more efficiently attained at relatively low ejection angles (20 degrees-40 degrees). Finally, the occurrence of Australasian microtektites (similar to 0.8 Ma old) on specific glacial surfaces of the Antarctic bedrock constrains the glacial history of the East Antarctic Ice Sheet in Victoria Land. In particular, data from Allan Hills supports a glaciological scenario envisaging an extremely stable East Antarctic Ice Sheet over at least the last similar to 1 Ma in the inland catchment of the Mackay/David glaciers. This is consistent with the large accumulation of meteorites in the adjacent blue ice fields. (C) 2016 Elsevier B.V. and NIPR. All rights reserved.